PENENTUAN STRATEGI BERSAING PADA RAYHAN STEEL KOTA PEKANBARU MELALUI PENDEKATAN ANALISIS SWOT - Yoggy Wahyudi Yoggy Wahyudi; Wijayanto Gatot; Jushermi Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the Internal and External environment and Formulate alternative strategies for Rayhan Steel building stores to increase competitiveness. The research uses descriptive qualitative method supported by interviews to obtain the data used. Respondents in this study include Lecturer of Economics and Lecturer of Marketing Management as Economic experts, Public Works and Public Housing Office of Pekanbaru City, Central Statistics Agency of Pekanbaru City and Owner Rayhan Steel. in determining Informant Interviews researchers use Judgment sampling Techniques and use SWOT Analysis in strategizing alternatives. The results of this study: IE Matrix, Rayhan Steel is in the Grow and Build position and SWOT Matrix Rayhan Steel applies the SO (Strength-Opportunity) by using Strenght to take advantage of opportunities, through: 1) Increases cooperation relationships with construction entrepreneurs, 2) Maximizes Promotion and Technology Development, 3) Utilizing Strategic Locations to Develop businesses.Keywords: Competitive Strategy, SWOT Analysis, Internal Factors, External Factors